2018
DOI: 10.1038/s41598-018-30140-2
|View full text |Cite
|
Sign up to set email alerts
|

Y1 receptor deficiency in β-cells leads to increased adiposity and impaired glucose metabolism

Abstract: Insulin secretion from pancreatic β-cells is critical for maintaining glucose homeostasis and deregulation of circulating insulin levels is associated with the development of metabolic diseases. While many factors have been implicated in the stimulation of insulin secretion, the mechanisms that subsequently reduce insulin secretion remain largely unexplored. Here we demonstrate that mice with β-cell specific ablation of the Y1 receptor exhibit significantly upregulated serum insulin levels associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…A more exciting area of PYY research in recent times relates to the beneficial effects of PYY (1–36) at the level of the endocrine pancreas . The NPYR1 is abundantly expressed on pancreatic β cells, with local islet synthesis and secretion of PYY (1–36) also noted . Indeed, there is a suggestion that the impressive endocrine pancreatic benefits following Roux‐en‐Y gastric bypass surgery are linked to altered PYY secretion and enhanced NPYR1 activity .…”
Section: Introductionmentioning
confidence: 99%
“…A more exciting area of PYY research in recent times relates to the beneficial effects of PYY (1–36) at the level of the endocrine pancreas . The NPYR1 is abundantly expressed on pancreatic β cells, with local islet synthesis and secretion of PYY (1–36) also noted . Indeed, there is a suggestion that the impressive endocrine pancreatic benefits following Roux‐en‐Y gastric bypass surgery are linked to altered PYY secretion and enhanced NPYR1 activity .…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro experiments, addition of the NPY1R blocker BIBP3226 abolishes the potentiating effect of sitagliptin on insulin release, 28 while activation of NPY1R (and NPY4R, NPY5R) protects mouse and human islets from cytokine-induced apoptosis and restores their glucose responsiveness. 29 In vivo studies have also demonstrated that mice lacking NPY1R either in beta cells 42 or in osteoblasts 43 have impaired glucose tolerance, thus extending the impact of NPY signalling, that could be additionally modulated by NPY and pancreatic polipeptide, on glucose homeostasis beyond pancreatic tissue regulation. On the other hand, injection of lipidated-NPY analogues appears to be able to protect beta cells and reduce hyperglycaemia induced by multiple low doses of streptozotocin 29 thus mimicking the protective effect reported for PYY analogues.…”
Section: Pancreatic Pyy Can Contribute To the Regulation Of Insulin Smentioning
confidence: 98%
“…Comparison between male and female conditional knockout rodent models. Chao et al, 2011;Ste Marie et al, 2005;Baldock et al, 2007;Bertocchi et al, 2011Bertocchi et al, , 2020Statello et al, 2016;Longo et al, 2014Longo et al, , 2015Longo et al, , 2018Loh et al, 2018;Acton et al, 2019;Baldock et al, 2006;Allison et al, 2006;Shi et al, 2010;Tasan et al, 2010;McCall et al, 2013. ARC, hypothalamus arcuate nucleus; DMH, dorsomedial hypothalamus; HFD, high fat diet; nd, not determined; PP, pancreatic polypeptide; VGAT, vesicular GABA transporter; WAT, white adipose tissue. For references: blue characters, study performed only on males; black characters, study performed in both males and females.…”
Section: Tablementioning
confidence: 99%